Drug Market Violence: Virtual Anarchy, Police Pressure, Predation, and Retaliation. (March 2015) - Jacques, Scott; Allen, Andrea
Drug consumption and addiction are known to increase the incidence of violent and property crimes. For this reason, governments prohibit the trade in some psychoactive substances and vigorously enforce the law. The unfortunate consequence of this governmental control is that it increases drug market violence. This article examines how drug prohibition and its enforcement affect violence among illicit drug traders. Two processes are considered: the role of virtual anarchy and police pressure in exposing illicit drug traders to predation and motivating them to retaliate. After reviewing the empirical literature bearing on these theories, this article concludes by outlining what is needed to move the field forward.